On the nature of the electrochemically synthesized hard Fe-0.96 mass pct C alloy film - Haseeb, A.S. Md. Abdul; Hayashi, Y.; Masuda, M.; Arita, M. (Springer Verlag (Germany), 2002)
A hard Fe-0.96 mass pct C alloy with a hardness value of 810 HV has been electrochemically synthesized from a ferrous sulfate bath containing a small amount of citric acid and L-ascorbic acid. The nature of the alloy has been investigated by a number of techniques, including X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Mossbauer spectroscopy, differential scanning calorimetry (DSC), and magnetic measurements. The decomposition behavior of the alloy is also studied and compared-with that of thermally prepared martensite. It has been found that the electrochemically deposited Fe-C alloy exists in a state that is ahead of the freshly quenched state of martensite. It is suggested that the state of the electrochemically deposited Fe-0.96 mass pct C alloy corresponds to the state of thermal martensite, which had been heated to stage I of tempering.